1982
DOI: 10.1182/blood.v59.5.971.bloodjournal595971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HLA Bw4/Bw6 compatibility on platelet transfusion responses of refractory thrombocytopenic patients

Abstract: Platelet transfusions from donors matched for cross-reactive antigens have been shown to be effective in providing hemostasis in alloimmunized thrombocytopenic patients. A significant number of these transfusions, however, fail to provide posttransfusion platelet recoveries. We investigated incompatibility in the Bw4/bw6 system as a possible explanation for these failures. The Bw4/Bw6 system is a biallelic antigen system closely associated with HLA-B. HLA-B locus antigens that are cross-reactive frequently dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…24,26 Fifteen studies were prospective 13,16,[24][25][26][27][28][29][30][31][32][33][34]45,46 and 14 were retrospective. 12,17,22,[35][36][37][38][39][40][41][42][43][44]47 Twenty-one of the nonrandomized studies focused on patients with refractory thrombocytopenia, 12 Two full text articles identified by authors n = 2…”
Section: Rctmentioning
confidence: 99%
See 4 more Smart Citations
“…24,26 Fifteen studies were prospective 13,16,[24][25][26][27][28][29][30][31][32][33][34]45,46 and 14 were retrospective. 12,17,22,[35][36][37][38][39][40][41][42][43][44]47 Twenty-one of the nonrandomized studies focused on patients with refractory thrombocytopenia, 12 Two full text articles identified by authors n = 2…”
Section: Rctmentioning
confidence: 99%
“…25,28 Nineteen studies indicated single-donor PLTs were used. 12,13,16,24,[26][27][28][30][31][32][33][34]37,38,40,41,[43][44][45] The assessment of study quality is displayed in Table S3 (available as supporting information in the online version of this paper). Nine of the 29 studies did not specify the source of sample of patients, that is, how patients were recruited.…”
Section: Number Of Citations Included N = 29mentioning
confidence: 99%
See 3 more Smart Citations